Face-to-Face Mentoring, Remotely Supervised Home Exercise Prehabilitation to Improve Physical Function in Patients Awaiting Kidney Transplantation: A Randomized Clinical Trial - Ma, Xiaojie; Zhang, Zaozhang; Peng, Mengsi; Yao, Bonuan; Jiang, Hongtao; Ji, Xuanfu; You, Yong (Frontiers in Psychology, 2022)
OBJECTIVE: This study aims to explore the feasibility, safety, and effectiveness of home exercise prehabilitation on a new social platform for remote guidance to optimize the physical function of patients with end-stage renal disease awaiting kidney transplantation and provide scientific guidance on home prehabilitation exercises for patients awaiting kidney transplantation. METHODS: The subjects of this randomized clinical trial were randomly divided into the test and control groups. The control group maintained their exercise habits, while the trial group was given a 12-week personalized home prehabilitation exercise prescription (aerobic exercise + functional resistance exercise + flexibility exercise) on a new social platform with remote guidance. The participants’ physical and cardiorespiratory fitness, quality of life, and psychological functioning were assessed before and after the intervention. The 6-min walk test (6MWT) walking distance and its percentage of attainment, the handgrip, the 5 repetition-sit-to-stand test, and the 4-m gait speed were used as primary outcome indicators, while the SF-36 (health survey summary table) and the Hospital Anxiety and Depression scale were used as the secondary outcome indicators. RESULTS: After 12 weeks of intervention, the changes in the 6MWT measured distance (+44.9 ± 40.2, P = 0.001) and the percentage of 6MWT measured distance achieved (+6.8 ± 5.7, P = 0.001), the handgrip (+2.7 ± 4.3, P = 0.028), the 5-sit-to-stand test (-1.1 ± 1.4, P = 0.005), and the 4-m walking speed (-0.3 ± 0.4, P < 0.001) of the test group (n = 21) improved significantly. In the control group (n = 16) , the changes in the 6MWT measured distance (-13.1 ± 57.2), the 6MWT measured distance attainment percentage (-2.1 ± 9.1), the handgrip (-0.1 ± 2.5), the 5-sit-to-stand test value (0.6 ± 2.2), and the 4-m walking speed (0.2±0.5) decreased slightly but showed no significant difference. No significant improvement in anxiety, depression, and SF-36 was noted in both the test and control groups. CONCLUSION: The remote coaching of home exercise prehabilitation on a new social platform significantly improves the physical and cardiopulmonary fitness of patients with end-stage renal disease awaiting kidney transplantation. This treatment is safe and feasible in this population.